ANALISIS HUBUNGAN TINGKAT PENGETAHUAN, KEDISIPLINAN, REWARD AND PUNISHMENT DOKTER SPESIALIS TERHADAP KETIDAKLENGKAPAN PENGISIAN RESUME MEDIS RAWAT INAP DI RUMAH SAKIT UMUM DHARMA YADNYA DENPASAR - Amanda Tizza Ayunadha P; Agus Donny Susanto; Made Nyandra (LPPM Universitas Dhyana Pura, 2018)
ABSTRACTMedical resume is one of the important parts to provide all information relating to patients. Therefore a medical resume must be filled in completely. Doctors who fill out medical resumes act as the main person in charge of completing medical resume filling. With a complete medical resume, it will be able to improve the quality of medical records. The purpose of this study was to determine the relationship between the level of knowledge, discipline, reward and punishment of specialist doctors with the incompleteness of filling in the medical resume of inpatients at the Dharma Yadnya General Hospital, Denpasar. The design of this study was quantitative analytic descriptive with cross sectional research type. The research method used was interviews, observations, questionnaires, and check lists with a sample of 14 specialists at Denpasar Dharma Yad Hospital. Of the 414 medical record resumes studied, found a medical resume inpatient that was not fully filled in amounted to 37 and the complete numbered 377 medical resumes. The results of this study indicate that there is a relationship between the level of knowledge with p = 0.000 <0.05, discipline with p = 0.002 <0.05, reward and punsihment with p = 0.012 <0.05 with the incompleteness of medical resumes. The conclusion of this study shows that the level of knowledge, discipline, reward and punishment of specialist doctors is related to the incompleteness of filling in medical resumes.Keywords: incompleteness, level of knowledge, discipline, reward and punishmentABSTRAKResume medis merupakan salah satu bagian penting dalam membantu segala informasi yang menyangkut pasien, oleh karena itu resume medis harus diisi secara lengkap. Dokter yang mengisi resume medis sebagai penanggung jawab utama terhadap kelengkapan pengisian resume medis dengan lengkapnya resume medis maka akan menjadikan mutu rekam medis yang baik. Tujuan penelitian ini adalah untuk mengetahui hubungan tingkat pengetahuan, kedisiplinan, reward and punishment dokter spesialis terhadap ketidaklengkapan pengisian resume medis rawat inap di RSU Dharma Yadnya Denpasar. Rancangan penelitian ini adalah deskriptif analitik kuantitatif dengan jenis penelitian cross sectional. Metode penelitian ini wawancara, observasi, kuisioner, dan check list dengan sampel penelitian ini adalah 14 orang dokter spesialis di RSU Dharma Yadnya Denpasar. Ketidaklenglapan pengisian resume medis rawat inap berjumlah 37 resume medis dan yang lengkap pengisiannya berjumlah 377 resume medis dari 414 resume medis. Hasil penelitian ini mendapatkan hasil adanya hubungan tingkat pengetahuan terhadap ketidaklengkapan resume medis dengan nilai p= 0,000<0,05, kedisiplinan dengan nilai p=0,002<0,05, reward and punsihment dengan nilai p=0,012<0,05. Kesimpulan dari penelitian ini yaitu tingkat pengetahuan, kedisiplinan, reward and punishment dokter spesialis memiliki hubungan dengan ketidaklengkapan pengisian resume medis.Kata kunci : Ketidaklengkapan, tingkat pengetahuan, kedisiplinan, reward and punishment